Consequences of the Potential Gauging Process for Modeling Electromagnetic Wave Propagation - Thomas Reum (IEEE Open Journal of Antennas and Propagation)
This predominantly theoretical article focuses on a qualitative discussion of peculiarities, which are introduced in practical electromagnetic (EM) wave propagation scenarios when the gauge for the electrodynamic potentials is not chosen in accordance to the appropriate space-time metric of the underlying physical framework. Based on ordinary vector calculus, this is done for the viewpoint of radio frequency (RF) engineers by using two examples of guided EM waves: one large-scale case of a terrestrial scenario and one small-scale case involving a device level setup. Readers may benefit especially from this practical orientation, since gauging is often analyzed primarily mathematical by solely arguing on terms of equations instead of discussing concrete applications. The provided context aims to enhance the usual perspective and is applicable for a wide class of situations involving various wave types at any frequency.